Recent Root Canal Instruments and Techniques: A Review - Zeena T. Abdulhadi Alani (Institute of Medico-legal Publications Pvt Ltd, 2020)
In this article the properties and advantages of NITI alloy were presented with the development of new types of endodontic files and instrumentation techniques. Each new one was designed to solve disadvantages present in older one. NITI files always considered suitable for negotiation of curved canals, this automatically will reduce any possibility of some problems like transportation, ledge formation and zipping within the canal. Cleaning and shaping of the root canal space is the most important to create a sterile area, organisms free. In order to reach this goal (sufficient information of current development of instruments and instrumentation techniques is needed). With the new versions which are rapidly becoming available, the Dentist may find it a little bit difficult to choose the most suitable file and technique for an individual case. Practitioners must always keep in mind that benefits and weaknesses is present in most file systems. In other hand clinical experience, usage safety, handling properties and outcomes of the case, should decide a particular design fate. Conclusion: Endodontic treatment files and techniques are very rapidly developed and this is the most important point,since each new design or technique will supply advantages which improve the endodontic treatment work and prognosis.